Hospital volume and short‐term outcomes after cytoreductive nephrectomy. Issue 7 (25th March 2018) - Xia, Leilei; Strother, Marshall C.; Taylor, Benjamin L.; Chelluri, Raju R.; Pulido, Jose E.; Guzzo, Thomas J.
Abstract : Purpose: To investigate the impact of hospital volume on short‐term outcomes after cytoreductive nephrectomy (CN) for metastatic renal cell carcinoma (mRCC). Methods: We identified mRCC patients who underwent CN from 2006 to 2013 in the National Cancer Database. Annual hospital CN volume was categorized as high (top 20th percentile) and low. Multivariable logistic regressions were used to compare 30‐day mortality, 90‐day mortality, prolonged length of stay (PLOS, ≥7 days), and 30‐day readmission rates. Sensitivity analyses were performed with hospital volume considered as a continuous variable. Results: A total of 9789 patients were included with high‐volume ( n  = 1916) defined as ≥8 cases and low‐volume ( n  = 7873) as 1‐7 cases annually. Multivariable logistic regression showed that high‐volume was associated with lower odds of 30‐day mortality (OR = 0.69, P  = 0.013), 90‐day mortality (OR = 0.65, P  < 0.001), PLOS (OR = 0.82, P  = 0.002), and 30‐day readmission (OR = 0.78, P  = 0.028). Sensitivity analyses showed that increasing hospital volume (per case) was associated with lower odds of 30‐day mortality (OR = 0.965, P  = 0.008), 90‐day mortality (OR = 0.966, P  < 0.001), PLOS (OR = 0.982, P  = 0.001), and 30‐day readmission (OR = 0.975, P  = 0.012). Conclusion: Higher hospital volume was associated with better short‐term outcomes after CN. Future studies are needed to validate our findings and explore the potential components leading to better outcomes in the higher volume hospitals.